From the plastics manufacturing process to the way to the oceans - Caldas , Maria Catarina de Farias; Oliveira, Kaio Wêdann de; Santos , Júlio Cesar Vasconcelos dos; Monteiro, Eliana Cristina Barreto; Takaki , Galba Maria Campos (Seven Editora, 2023)
Plastics are by-products of origin from the petroleum industry, derived from oil and from the extraction of raw materials in the process of refining crude oil. In refineries, oil is fractionated into various types of organic materials, such as naphtha, gasoline, kerosene, and lubricating oils. From the naphtha that is extracted by cracking substances that give rise to conventional plastic. The last step to carry out the production of plastics is polymerization, where polymers arise, where each one differs from the other, arising from this whole process, thermoplastics, and thermosets. Therefore, it is possible to find plastics, ethylene, and propylene, such as polyethylene, polypropylene, polyvinyl chloride, epoxy resin, polyester, phenolic, silicones, and the most diverse types of plastics. Due to the extent and structure of polymers, they can be non-rigid plastics that can have different applicability. Thermosetting plastics, which do not melt by heating, are insoluble and non-recyclable and with differentiated use in various sectors. However, the widespread disorderly disposal of plastics has come to represent one of the biggest ecological problems in the pollution of marine environments, representing 80% of the garbage found in the oceans, being composed mainly of bags and bottles, among other contaminants. The outlook until 2040 shows that the volumes of plastic flowing into the sea could be tripled, with the expectation that it can present an annual quantity calculated between 23 and 37 million tons. Given this reality, studies focused on technologies capable of minimizing the impacts caused by these pollutants on environments have grown exponentially. Thus, the search for alternative measures for the reuse of plastics, being chemical, mechanical or energy recycling one of the solutions for the transformation of plastics, from the areas of biotechnology to civil construction, with the sole objective, to reduce the presence and damage caused by plastic. The highest concentration of garbage may be found in coastal regions and on the seabed. In this context, this review presents the problems of environmental pollution in the oceans caused by rigid plastics and non-rigid plastics, as well as studies directed at the displacement of plastics in the oceans and current technologies to remedy the problem. DOI:https://doi.org/10.56238/alookdevelopv1-063